The role of non-timber forest products in reducing rural poverty in Burkina Faso - Issoufou Ouedraogo; Eugenie Maiga; Lars Esbjerg (Journal of Agriculture and Environment for International Development)
Using data collected in 2023 on five hundred and thirty (530) randomly selected rural households in two regions of Burkina Faso, this research investigates the contribution of Non-Timber Forest Products (NTFP) exploitation to rural poverty reduction using two different approaches. Firstly, it considers NTFP income as an "exogenous transfer", which is added to total household income, and compares the Foster, Greer and Thorbecke (FGT) poverty indices calculated with and without NTFP income. Secondly, it considers NTFP income as a "potential substitute" for other household income and simulates the counterfactual of what rural household income and poverty would be in the absence of access to NTFPs. The results show that in the absence of NTFPs, rural poverty would be much higher and deeper. These results suggest that rural development policies focused on the sustainable exploitation of these products are potentially feasible.